2017
DOI: 10.4269/ajtmh.16-0753
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Scabies and Impetigo in Relation to Demographic and Residential Characteristics: Baseline Findings from the Skin Health Intervention Fiji Trial

Abstract: Scabies and associated impetigo are under-recognized causes of morbidity in many developing countries. To strengthen the evidence base for scabies control we undertook a trial of mass treatment for scabies. We report on the occurrence and predictors of scabies and impetigo in participants at baseline. Participants were recruited in six island communities and were examined for the presence of scabies and impetigo. In addition to descriptive analyses, logistic regression models were fit to assess the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
67
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 27 publications
12
67
1
4
Order By: Relevance
“…In the last study, it was observed that people with scabies were 2.8 times more likely to develop impetigo. Households with four or more people sharing the same room were more likely to develop scabies and impetigo compared to households with rooms occupied by a single individual . In Indigenous communities in Northern Australia, the prevalence of superinfected scabies in children aged less than 5 years was 12% .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In the last study, it was observed that people with scabies were 2.8 times more likely to develop impetigo. Households with four or more people sharing the same room were more likely to develop scabies and impetigo compared to households with rooms occupied by a single individual . In Indigenous communities in Northern Australia, the prevalence of superinfected scabies in children aged less than 5 years was 12% .…”
Section: Discussionmentioning
confidence: 96%
“…In an Indian study, secondary pyoderma was detected in 42.8% of children with scabies . Three studies were carried out in Fiji Islands . The first one showed that impetigo was more common in Indigenous Fijian children when compared with children of other ethnicities .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scabies is one of the most important skin diseases worldwide particularly in developing countries, caused by mite Sarcoptes scabiei [1,2]. Sexually transmitted is the main way of infection and is a common between family members [3].…”
Section: Introductionmentioning
confidence: 99%